The Association between Perceived Discrimination and Suicide among Homosexuals: The Role of Self-Esteem as Mediator - Tan, Soon Aun; Tay, Wei Man; Neoh, Magdelene Ee Yin; Wong, Hui Wen (Makara Human Behavior Studies in Asia, 2018)
Because of Malaysia’s conservative society, its homosexual citizens are often marginalized and discriminated. Past studies have shown a significant difference in psychological well-being between homosexuals and their heterosexual counterparts, which is attributed to differences in social treatment. Existing studies have discussed the underlying process of the relation between perceived discrimination and suicidal ideation among homosexuals globally. Therefore, this study aimed to investigate the relation between perceived discrimination and suicidal thoughts among homosexuals in Malaysia through the mediating effect of self-esteem. Research subjects were composed of400 self-identified homosexuals who participated in an online survey. TheSuicidal Ideation Attributes Scale, Modified Acculturative Stress Scale, andRosenberg Self-Esteem Scale were used to measure the variables under investigation. Results indicated a negative significant correlation between the perceived discrimination–self-esteem link and between the self-esteem–suicidal ideation link among homosexuals. Positive relations were found between perceived discrimination and suicidal ideation. Moreover, a significant mediating effect of self-esteem was found in the link between perceived discrimination and suicidal ideation, which showed that high perceived discrimination and low self-esteem are risk factors for suicidal thoughts. Hence, besides promoting psychological betterment among homosexuals, self-empowerment seems critical and necessary to reduce suicidal ideation risk among homosexuals.